THE REVITALIZATION OF BATAKNESE LANGUAGE IN TANJUNG BALAI : A STUDY CASE AT SEI TUALANG RASO TANJUNG BALAI, NORTH SUMATERA - RANI FAIRUS (LP2MTBM MAKARIOZ, 2020)
The study was conducted to find out the revitalization of Bataknese language in Tanjung Balai. The subject of the study was 123 households in three streets in Sei Tualang Raso subdistrict, Tanjungbalai city. This research design was qualitative descriptive design. The instrument for collecting the data was questionnaire. The data was analyzed by reading the result of questionnaires which have been filled by respondents. The result of analysis showed that: 1) Increase the proficiency speakers of Bataknese language. The skill of the language proficiency includes listening, speaking, reading and writing. (2) Grow positive attitude towards bataknese language. (3) Expand the use of bataknese language distribution. Spreading the use of bataknese language can be done by means of print, electronic, device cyberspace.